Preventive Education on the Phenomena of Radicalism and Extrimism in Islamic Educational Institutions - Maulidi, Achmad; Khaliq, Abd.; Amirullah, Bagus (Maharot : Journal of Islamic Education, 2024)
Lately, our country, which is famous for its diversity, has been shocked by cases of radicalism and extremism, ironically this phenomena has occurred in many educational institutions, even allegedly radical and extremist seeds have the potential to grow in educational institutions. The purpose of this study is to examine in depth how the implementation of moderation and tolerance education in Islamic educational institutions as a preventive effort for the phenomenon of radicalism and extremism. This research is a qualitative research type of case study, using semi-structured interview methods, participant and non-participant observation and documentation as data collection methods. While data analysis includes data condensation stages, data presentation and conclusion drawing. The results of this study indicate that moderation and tolerance education as a preventive effort for the phenomena of radicalism and extremism is internalized in students through intra and extra activities which are also integrated in the hidden curriculum.